Clonal Diversity, Virulence Potential and Antimicrobial Resistance of Escherichia coli Causing Community Acquired Urinary Tract Infection in Switzerland - Nüesch-Inderbinen, Magdalena T.; Baschera, Melinda; Zurfluh, Katrin; Hächler, Herbert; Nüesch, Hansjakob; Stephan, Roger (Frontiers in Microbiology, 2017)
Objectives: The aim of this study was to assess the clonal structure, virulence potential and antibiotic susceptibility of uropathogenic Escherichia coli (UPEC) isolates causing community acquired urinary tract infection (CAUTI) in unselected primary care patients in Switzerland. Methods: We performed multilocus sequence typing, virulence factor determination, and phenotypic and genotypic antimicrobial resistance testing on 44 non-duplicate UPEC isolates. Results: Twenty-seven different sequence types (STs) were identified. Major UPEC clones were represented by 19 (43.2%) of the isolates, including E. coli ST131, ST69 (both 13.6%), ST73 (6.8%), ST10 (4.5%), ST127, ST140, (both 2.3%). Five (11.4%) isolates belonged to ST141. Aggregate virulence factor (VF) scores were highest among isolates belonging to ST127 and ST141. Overall, 50% of the isolates were susceptible to all 12 antimicrobials tested, and all isolates remained susceptible to fosfomycin and nitrofurantoin. Resistance to sulfamethoxazole and ciprofloxacin were found in 31.8%, and 15.9% of the isolates, respectively. Plasmid-mediated resistance genes were detected in ST69 and ST131 and included aac(6')-Ib-cr (2.3% of all isolates) blaCTX-M-14 and blaCTX-M-15 (9%), and mph(A) (13.6%). None of the isolates tested positive for mcr-1 or mcr-2. Conclusions: Our results show that CAUTI in Switzerland is caused by a wide variety of UPEC STs for which fosfomycin remains a good treatment option. We suggest that ST141 is an emerging clone associated with UTI in the community, and warrants closer attention. Moreover, the high rate of E. coli harboring mph(A) from patients without a history of antimicrobial therapy or hospitalization indicates that UPEC is an important reservoir for mph(A).